PEMBERDAYAAN IMAN KELUARGA KATOLIK MELALUI KEGIATAN LINGKUNGAN DI STASI SUMBER BENING DAN WIDODAREN PAROKI ST. YOSEF NGAWI - Wilhelmus, Ola Rongan (Lembaga Penelitian STKIP Widya Yuwana, 2024)
Many Catholic couples and families today prefer to choose the easy and shortcut way to solve the problems and challenges related to the family and marriage life. For example, problems of infidelity, economics, domestic violence are often resolved by divorce. This settlement proved to have many negative impacts on the family life. Recognizing these various family challenges and problems, the Surabaya Diocese's pastoral activities during 2023 focussing on the pastoral theme: Living Christ in the Family